Sustainability study and SWOT analysis of mixed biofuel blends in engine at various injection pressure analysed by experimentally and statistically - Jagan Padmanaban; Annamalai Kandasamy; Elumalai Perumal Venkatesan; Sreekanth Sura; C. Ahamed Saleel; Nasim Hasan; Lin Zhenxiong (Scientific Reports)
Abstract This study aims to reduce engine emissions while maintaining engine performance and providing a sustainable fuel source for long-term use. It introduces a novel approach by combining pine oil (PO) and lemon grass oil (LGO) with diesel fuel in a specific ratio (10% PO + 10% LGO + 80% Diesel). This work is innovative in that it employs these two distinct low-viscosity biofuel blends in conjunction with diesel fuel in an agricultural engine, resulting in reduced carbon footprints in the tailpipe. The blend tested in a single-cylinder diesel engine showed that using PO and LGO together reduced UHC emissions by 42.96%, CO emissions by 20.79%, and smoke emissions by 26.26%, while keeping the BTE the same. However, there was a 7.16% rise in NOx emissions. To decrease NOx emissions, antioxidants—250 mg of p-phenylene diamine (10% PO + 10% LGO + 80% + 250 mg PPDA) and 100 mg of butylated hydroxy toluene (10% PO + 10% LGO + 80% + 100 mg BHT) were added. The blends were injected at different injection pressures of 300 bar, 450 bar, and 600 bar, which can result in a reduction in NOx emissions of up to 11.78% and 10.99% for B2 + 300 bar and B3 + 300 bar, respectively. We used the SWOT study to evaluate the advantages and disadvantages of the mixed fuel, and employed the PUGH Matrix decision tool to carry out the sustainability assessment. The results showed that the blend (10% PO + 10% LGO + 80% Diesel + Antioxidant + 600 bar) is a sustainable fuel, considering environmental, social, and economic factors to be more feasible than pure diesel.